Rekonstruksionisme dan Pedagogik Transformatif dalam Kurikulum Pendidikan Ilmu Pengetahuan Sosial di Indonesia - Surbayana Surbayana; Siska Nurazizah Lestari (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Social Studies education in Indonesia continues to experience tension between the transmission of knowledge and the imperative to cultivate critical, participatory, and socially responsible citizens. This study examines how reconstructionism can function as a curricular epistemology capable of addressing these challenges within the context of digital-era citizenship. Employing a philosophical-comparative approach combined with a genealogical analysis of Indonesian Social Studies curricula from the 1975 Curriculum to the Merdeka Curriculum (2022), the study investigates the philosophical continuity and transformation of reconstructionist ideas. The findings reveal three major gaps: the absence of an operational framework for classroom implementation, inconsistencies between reconstructionist curricular objectives and assessment practices, and the limited incorporation of contemporary learning theories into reconstructionist discourse. In response, this article proposes Stratified Reconstructionism, a multi-layered conceptual model integrating four traditions of Social Studies education—citizenship transmission, social sciences, reflective inquiry, and social criticism—within a transformative pedagogical cycle. Drawing upon Vygotsky’s Zone of Proximal Development and Ausubel’s meaningful learning theory, the model facilitates students’ progression from understanding social realities to critical reflection and civic action. The study argues that reconstructionism provides a coherent philosophical foundation for strengthening democratic citizenship, critical thinking, and social engagement in Indonesian Social Studies education.